Health information needs of families attending the paediatric emergency department. Issue 4 (10th January 2011) - Wahl, Holger; Banerjee, Jay; Manikam, Logan; Parylo, Craig; Lakhanpaul, Monica
Abstract : Background: The National Health Service Plan (July 2000) aimed to empower patients with more influence upon their own treatment. Provision of additional educational health information (AEHI) serves to inform families about health conditions and to allow them to manage their own health after discharge. However, to date, it is unknown how parents or carers perceive this information. Objectives: To identify parents' and carers' views towards the current provision of AEHI following discharge of their child from an emergency care service, to assess their needs concerning AEHI and to provide recommendations for subsequent research. Methods: Between 11 April and 19 June 2007, a piloted questionnaire was handed out at random times to each family attending the children's emergency department while they were waiting to be clinically assessed. 1046 families chose to participate and answered questions about their ethnicity, language preference and ability, media access and their sources of health information. The data were analysed using descriptive methods. Results: A majority of families wish to receive hospital AEHI as leaflets. Additionally, families frequently use a variety of other resources such as extended family and friends and the Internet to address their information needs. Poor literacy is a barrier to understanding in 15.6% of the study population. 73% of carers with children aged between 10 and 16 years wish their children to receive AEHI. Conclusions: The authors identified a gap in the provision of health information with respect to appropriate educational material for children and young persons, for families with poor literacy skills and those with language barriers.